Confirmatory factorial analysis of the Maslach Burnout Inventory - Human Services Survey in health professionals in emergency services - Sandra de Souza Pereira; Joana Fornés-Vives; Sara Guadalupe Unda-Rojas; Gerson Alves Pereira-Junior; Mario Francisco Juruena; Lucilene Cardoso (Universidade de São Paulo, 2021)
Objective: to confirm the factorial validity of the Maslach Burnout Inventory - Human Services Survey version in a sample of health professionals from the emergency services. Method: a quantitative, exploratory, descriptive and analytical study. Two hundred and eighty-two health professionals participated in the study. For data collection, a sociodemographic questionnaire and the Maslach Burnout Inventory were used. The psychometric sensitivity for the MBI-HSS items was estimated by measures of central tendency, variability and the distribution shape. Internal consistency was estimated using Cronbach's alpha coefficient and the adequacy of the sample was verified using the Kaiser-Meyer-Olkin (KMO) index. As indexes for assessing the quality of fit of the model, the chi-square ratio by the degrees of freedom (χ2/DoF), the comparative fit index (CFI), the goodness of fit index (GFI), the Tucker Lewis index (TLI) and the root mean square error of approximation (RMSEA) were considered. To test data fit, the maximum likelihood method was used. Results: the three-factor structure of the Maslach Burnout Inventory was confirmed. Items 9, 12, 15 and 16 had a factorial weight below what was considered appropriate and were removed from the model. The second order hierarchical model with the aforementioned modifications presented an adequate adjustment to the data and can be considered the best and most parsimonious model tested according to the information theory indexes. The internal consistency of the instrument's factors was recalculated considering the exclusion of the items and the three factors were considered adequate. Conclusion: the results obtained show that the Maslach Burnout Inventory is a reliable and factorially valid instrument for measuring the burnout syndrome in emergency service professionals in Brazil.